CDK2 regulates aminoglycoside-induced hair cell death through modulating c-Jun activity: Inhibiting CDK2 to preserve hearing - Tao, Litao; Segil, Neil (Frontiers in Molecular Neuroscience, 2022)
Sensory hair cell death caused by the ototoxic side effects of many clinically used drugs leads to permanent sensorineural hearing loss in patients. Aminoglycoside antibiotics are widely used and well-known for their ototoxicity, but the molecular mechanisms of aminoglycoside-induced hair cell death are not well understood. This creates challenges in our attempts to alleviate or prevent such adverse side effects. Here, we report a regulatory role of CDK2 in aminoglycoside-induced hair cell death. Utilizing organotypic cultures of cochleae from neonatal mice, we show that blocking CDK2 activity by either pharmaceutical inhibition or by Cdk2 gene knockout protects hair cells against the ototoxicity of gentamicin—one of the most commonly used aminoglycoside antibiotics—by interfering with intrinsic programmed cell death processes. Specifically, we show that CDK2 inhibition delays the collapse of mitochondria and the activation of a caspase cascade. Furthermore, at the molecular level, inhibition of CDK2 activity influences proapoptotic JNK signaling by reducing the protein level of c-Jun and suppressing the gentamicin-induced upregulation of c-Jun target genes Jun and Bim. Our in vivo studies reveal that Cdk2 gene knockout animals are significantly less sensitive to gentamicin ototoxicity compared to wild-type littermates. Altogether, our work ascertains the non-cell cycle role of CDK2 in regulating aminoglycoside-induced hair cell apoptosis and sheds lights on new potential strategies for hearing protection against ototoxicity.